Exploring the energy efficiency for Search and Rescue operations over LoRa - Christos Bouras; Apostolos Gkamas; Spyridon Katsampiris (11th IFIP International Conference on New Technologies, Mobility and Security (NTMS' 2021), April 19 - 21, 2021, Paris, France, 2021)
The Internet of Things (IoT) is one of the pioneering domains of Computer Science and Engineering, that comes to solve a plethora of real-life problems. One of the most promising technologies that aim to provide long-distance transmission while retaining energy consumption at low levels, is Long Range (LoRa). In this paper, a thorough study of the energy efficiency in LoRa based Search and Rescue (SAR) project for people with special needs, called Wearable based Search And Rescue system (WeSAR) is presented. After research the authors propose a LoRa based system, taking into consideration the energy efficiency. The results of the proposed mechanism are encouraging in terms of energy consumption, and the battery can last enough for the majority of the SAR operations, even when the battery is not fully charged. Also, there is no deterioration in terms of the delivery ratio of the network which is important for localization algorithms.